Stratospheric Gravity Waves Impact on Infrasound Transmission Losses Across the International Monitoring System - C. Listowski; C. C. Stephan; A. Le Pichon; A. Hauchecorne; Y.-H. Kim; U. Achatz; G. Bölöni (Pure and Applied Geophysics, 2025)
The international monitoring system (IMS) has been put in place to monitor compliance with the comprehensive nuclear-test-ban treaty (CTBT). Its infrasound component, dedicated to the monitoring of atmospheric events, gives also room to civil applications (e.g. monitoring of volcanic eruptions, meteorites, severe weather). Infrasound detection capabilities are largely determined by the state of the middle atmosphere. This requires an accurate knowledge of the atmospheric processes at play. More particularly internal gravity waves (GW) pose a challenge to atmospheric modelling because of unresolved processes. Using high-resolution simulation outputs over winter 2020 (20 January–1 March) we present a method to assess the impact of GW on infrasound surface transmission losses across the IMS. We validate the method by comparing simulated GW perturbations to GW lidar observations at Observatoire de Haute-Provence in France, and satellite-based GW energy estimations globally. We perform propagation simulations using atmospheric specifications where GW are filtered out and kept in, respectively. We demonstrate that the largest impact of GW across the IMS is not where GW activity is the largest, but rather where GW activity combines with infrasound waveguides not firmly set in a given direction. In northern winter, the largest variations of transmission losses at 1 Hz due to GW occur in the southern (summer) hemisphere in the direction of the main guide (westward propagation), with average values ranging between 10 and 25 dB in the first shadow zone. It corresponds to an average signal amplification of at least a factor 5 to 15, while this amplification is around 2 to 5 for the main guide in the northern winter hemisphere (eastward propagation).